A Two‐Coordinate Cobalt(II) Imido Complex with NHC Ligation: Synthesis, Structure, and Reactivity. (31st August 2015) - Du, Jingzhen; Wang, Linbo; Xie, Meihua; Deng, Liang
Abstract The synthesis, structural characterization, and reactivity of the first two‐coordinate cobalt complex featuring a metal–element multiple bond [(IPr)Co(NDmp)] (4; IPr=1, 3‐bis(2′, 6′‐diisopropylphenyl)imidazole‐2‐ylidene; Dmp=2, 6‐dimesitylphenyl) is reported. Complex 4 was prepared from the reaction of [(IPr)Co(η2‐vtms)2] (vtms=vinyltrimethylsilane) with DmpN3. An X‐ray diffraction study revealed its linear CCoN core and a short CoN distance (1.691(6) Å). Spectroscopic characterization and calculation studies indicated the high‐spin nature of 4 and the multiple‐bond character of the CoN bond. Complex 4 effected group‐transfer reactions to CO and ethylene to form isocyanide and imine, respectively. It also facilitated EH (E=C, Si) σ‐bond activation of terminal alkyne and hydrosilanes to produce the corresponding cobalt(II) alkynyl and cobalt(II) hydride complexes as 1, 2‐addition products.